Understanding COVID-19 Pandemic: Molecular Mechanisms and Potential Therapeutic Strategies. An Evidence-Based Review - Hanna R; Dalvi S; Sălăgean T; Pop ID; Bordea IR; Benedicenti S (Dove Medical Press, 2021)
Reem Hanna,1,2 Snehal Dalvi,1,3 Tudor Sălăgean,4 Ioana Delia Pop,4 Ioana Roxana Bordea,5,* Stefano Benedicenti1,* 1Department of Surgical Sciences and Integrated Diagnostics, Laser Therapy Centre, University of Genoa, Genoa, Italy; 2Department of Oral Surgery, Dental Institute, King’s College Hospital NHS Foundation Trust, London, UK; 3Department of Periodontology, Swargiya Dadasaheb Kalmegh Smruti Dental College and Hospital, Nagpur, India; 4Department of Land Measurements and Exact Sciences, University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, Cluj-Napoca, Romania; 5Department of Oral Rehabilitation, “Iuliu Hațieganu” University of Medicine and Pharmacy Cluj-Napoca, Cluj-Napoca, Romania*These authors contributed equally to this workCorrespondence: Reem HannaDepartment of Surgical Sciences and Integrated Diagnostics, Laser Therapy Centre, University of Genoa, Genoa, ItalyTel +39 0103537446Email reemhanna@hotmail.comTudor SălăgeanDepartment of Land Measurements and Exact Sciences, University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, Cluj-Napoca, RomaniaTel +40744707371Email tudor.salagean@usamvcluj.roAbstract: Initially, the SARS-CoV-2 virus was considered as a pneumonia virus; however, a series of peer reviewed medical papers published in the last eight months suggest that this virus attacks the brain, heart, intestine, nervous and vascular systems, as well the blood stream. Although many facts remain unknown, an objective appraisal of the current scientific literature addressing the latest progress on COVID-19 is required. The aim of the present study was to conduct a critical review of the literature, focusing on the current molecular structure of SARS-CoV-2 and prospective treatment modalities of COVID-19. The main objectives were to collect, scrutinize and objectively evaluate the current scientific evidence-based information, as well to provide an updated overview of the topic that is ongoing. The authors underlined potential prospective therapies, including vaccine and phototherapy, as a monotherapy or combined with current treatment modalities. The authors concluded that this review has produced high quality evidence, which can be utilized by the clinical scientific community for future reference, as the knowledge and understanding of the SARS-CoV-2 virus are evolving, in terms of its epidemiological, pathogenicity, and clinical manifestations, which ultimately map the strategic path, towards an effective and safe treatment and production of a reliable and potent vaccine.Keywords: SARS-CoV-2, COVID-19, virus pathogenicity, cytokines storm, diagnostic methods, immunotherapy, vaccine, antiviral, photobiomodulation therapy, PBMT, photodynamic therapy, PDT, clinical trials